Direct CO2 Electrolysis on Symmetric La0.8Sr0.2Cr0.5Fe0.5O3−δ-Zr0.84Y0.16O2−δ Electrode-Supported Solid Oxide Electrolysis Cells. Issue 2 (9th February 2021) - Cui, Changsong; Wang, Yue; Tong, Yongcheng; Zhan, Zhongliang; Chen, Chusheng; Wang, Shiwei
Abstract : La0.8 Sr0.2 Cr0.5 Fe0.5 O3− δ (LSCrF) is a mixed ionic and electronic conductor with excellent stability in both reducing and oxidizing atmospheres. Herein, we prepared a symmetric tri-layer structure of "porous YSZ-LSCrF ∣ dense YSZ ∣ porous YSZ-LSCrF" by the tape casting and lamination techniques. Porous scaffolds of 80 wt% LSCrF − 20 wt% YSZ showed good conductivities and reasonably high performance for direct CO2 electrolysis with a current density of 0.84 A·cm −2 at 850 °C. Infiltrating Sm0.2 Ce0.8 O2− δ (SDC) catalysts into both porous scaffolds enhanced their catalytic activities for CO2 reduction and oxygen evolution reactions, yielding an increased electrolysis current density of 1.3 A·cm −2 at 850 °C and 1.5 V. Impedance measurements showed a pronounced decrease in the total interfacial polarization resistance at 1.5 V, i.e., 0.34 vs 0.66 Ω·cm 2 . In addition, these symmetric cells exhibited good short-term stability at various voltages from 1.0 to 1.6 V.